Ability to Write Argumentative Paragraphs of Class X Multimedia 1 - Nur Indah; Endi Sunardi (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of the study was to describe the ability to write argumentative paragraphs, class X Multimedia 1 students of SMK Negeri 9 Muaro Jambi in the 2016/2017 academic year by applying conditions such as, (1) aspects of paragraph criteria which include introduction, body of argument, and conclusions, (2) paragraph aspects such as unity, coherence and development, (3) linguistic aspects which include grammar, word choice, and punctuation. Methodology: This research uses a descriptive-quantitative method. The instrument used is the argumentative paragraph writing test. The subjects of this study were 24 students in class X Multimedia 1 at SMK Negeri 9 Muaro Jambi. The research instrument was in the form of an argumentative paragraph writing test. Main Findings: The results showed that in general the ability to write argumentative paragraphs of class X Multimedia 1 SMK Negeri 9 Muaro Jambi was quite capable. The details are (1) the ability to apply argumentation criteria which include introduction, body of argument, and conclusions with a value of 4.3 (able), (2) the ability to apply the requirements of a good paragraph includes unity, coherence, and development with a value of 3.7 (quite capable ) and (3) the ability to apply linguistic requirements which include grammar, word choice, and spelling and punctuation with a score of 3.6 (quite capable). Novelty/Originality of this study: Based on this conclusion, it is suggested to Indonesian language teachers at SMK Negeri 9 Muaro Jambi to improve learning to write argumentative paragraphs. Especially the ability to apply criteria such as, (1) aspects of argumentation paragraphs including introduction, body of arguments and conclusions, (2) aspects of good paragraphs include unity, coherence and development, (3) linguistic aspects which include grammar, choice of words, spelling and marks read.